The Concept of Religious Tolerance in the History of Islamic Civilization - Kalatini, Zaid Tsabit Al; Rahman, Mohammad Taufiq; Haq, Mochamad Ziaul; Aziz, Fauzan Hilmi (Jurnal Iman dan Spiritualitas, 2025)
This study aims to discuss the concept of religious tolerance in the history of Islamic civilization. This study uses a qualitative approach by applying analytical descriptive methods. The results and discussion in this study show that the dynamics of religious tolerance in the history of Islamic civilization cannot be separated from the understanding of Muslims of the concept of tolerance and inter-religious relations sourced from the Qur'an and the instructions of the Prophet Muhammad, as reflected in the Charter of Medina, the Pact of Umar, the birth of Comparative Religion, the concept of Ahl Al-Dhimma, to the Caliphate system that regulates tolerance and religious freedom. The study concludes that the concept of religious tolerance in Islamic teachings has been realized in the historical reality of Islamic civilization.